2018
DOI: 10.7812/tpp/18-105
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experience of Patients, Staff, and Clinicians with Social Needs Assessment

Abstract: The impacts of unmet health-related social needs, such as homelessness, inconsistent access to food, and exposure to violence on health and health care utilization, are well-established. Growing evidence indicates that addressing these and other needs can help reverse their damaging health effects, but screening for social needs is not yet standard clinical practice. In many communities, the absence of established pathways and infrastructure and perceptions of inadequate time to make community referrals are ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 11 publications
3
69
0
Order By: Relevance
“…The finding that more patients were comfortable with social screening itself than with its documentation in the EHR is consistent with a recent study on social risk screening where participants reported concern with privacy and utilization of social risk data 33 and findings from other work describing patients' unease around sharing health data. 56,57 There are already calls for developing standards to protect social risk data in EHRs, 58 which is increasingly relevant in the context of new efforts to share data across sectors.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The finding that more patients were comfortable with social screening itself than with its documentation in the EHR is consistent with a recent study on social risk screening where participants reported concern with privacy and utilization of social risk data 33 and findings from other work describing patients' unease around sharing health data. 56,57 There are already calls for developing standards to protect social risk data in EHRs, 58 which is increasingly relevant in the context of new efforts to share data across sectors.…”
Section: Discussionsupporting
confidence: 87%
“…The survey also included the following participant characteristics based on their potential to impact screening acceptability: age, sex, race/ethnicity, educational attainment, income, preferred language (English or Spanish), self-or caregiver-reported child health, social risks, 41 interest in assistance with social risk factors, trust in clinicians, 29,33,42,43 prior healthcare-based social risk screening, prior healthcare-based receipt of social assistance, and prior discrimination within health care. 44,45 Previously validated survey items were utilized or adapted when available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey domains and question language were based on content from facilitator guides developed for and themes that emerged from qualitative focus groups and key informant interviews with 46 patients and 40 clinician leaders in KPSC. 16 Themes from the focus groups and key informant interviews fell into domains of patient experiences with social needs, patient attitudes toward social needs screening and intervention, and patient support for health system investment in social needs programs. These became the main constructs for our survey, and language from the focus group prompts were adapted to examine these domains of inquiry in the survey.…”
Section: Survey Development and Structurementioning
confidence: 99%